2006
DOI: 10.3892/or.15.3.603
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol stimulates the secretion of matrix metalloproteinases 2 and 9 in MCF-7 human breast cancer cells

Abstract: Abstract. Alcohol consumption is a well-established risk factor for hormone-dependent breast cancer. In vitro studies performed to understand the mechanisms by which ethanol acts on breast cancer cells have shown that this compound stimulates both proliferation and migration. In the present study, we show by gelatin zymography that, when exposed to ethanol, MCF-7 human breast cancer cells display a higher amount of active metalloproteinases (MMP) 2 and 9 in their culture medium. This increase is somewhat highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
3
24
1
Order By: Relevance
“…In agreement with previous studies, we found that estrogen supplementation prevented the downregulation of MMP-2 in the acute and chronic stages of LV remodeling (8,61). Similar estrogenic effects on MMP-2 expression were found in the ventricle and arteries of ovariectomized rats (27,61,64), rat uterus (48), and in cell culture studies (9,18). Estrogen also has a direct regulatory effect on MMP-2 expression in cardiac fibroblasts and vascular smooth muscle cells (18,34,53).…”
Section: Discussionsupporting
confidence: 78%
“…In agreement with previous studies, we found that estrogen supplementation prevented the downregulation of MMP-2 in the acute and chronic stages of LV remodeling (8,61). Similar estrogenic effects on MMP-2 expression were found in the ventricle and arteries of ovariectomized rats (27,61,64), rat uterus (48), and in cell culture studies (9,18). Estrogen also has a direct regulatory effect on MMP-2 expression in cardiac fibroblasts and vascular smooth muscle cells (18,34,53).…”
Section: Discussionsupporting
confidence: 78%
“…al. [47] show that alcohol stimulates the secretion of MMP2 and MMP9 from breast cancer cells. In our studies, alcohol activates MMP2 in breast cancer cells by promoting the cleavage of the pro-enzyme and transferring to an active enzyme.…”
Section: Alcohol-induced Aggressiveness Of Breast Cancermentioning
confidence: 99%
“…Pools of 3 gonad-mesonephros complexes from larvae were sonicated on ice in PY lysis buffer (Etique et al, 2006) for 5 sec (Branson sonifier 150, Branson Ultrasonics, Danbury, MA). After 10 min at 13,000 rpm centrifugation, supernatants were sampled and boiled for 5 min in Laemmli buffer.…”
Section: Western Blottingmentioning
confidence: 99%